Baseline peripheral blood leukocytosis: Biological marker predicts outcome in oropharyngeal cancer, regardless of HPV-status. (March 2018) - Gouw, Zeno A.R.; Paul de Boer, Jan; Navran, Arash; van den Brekel, Michiel W.M.; Sonke, Jan-Jakob; Al-Mamgani, Abrahim
Highlights: Leukocytosis has negative impact on outcome of OPC, regardless of HPV-status. The negative impact on outcome was even more pronounced in HPV-positive OPC. Patients with HPV-positive disease without leukocytosis have the best prognosis. Patients with HPV-negative disease with leukocytosis have the worst prognosis. This extremely simple marker might be used as a prognostic index in OPC. Abstract: Objectives: To study the prognostic value of abnormalities in baseline complete blood count in patients with oropharyngeal cancer (OPC) treated with (chemo) radiation. Methods and materials: The prognostic value of baseline complete blood count on outcome in 234 patients with OPC treated between 2010 and 2015 was examined in multivariate analysis together with other conventional prognostic variables including HPV-status, tumor stage, tumor and nodal size. Results: The 3-year overall survival (OS), disease-free survival (DFS), locoregional control (LRC), and distant control (DC) of the whole group were 74%, 64%, 79%, and 88%, respectively. Leukocytosis and HPV-status were the only significant prognosticators for OS and DFS at the multivariate analysis. Patients without leukocytosis had a significantly better DC compared to those with leukocytosis (92% and 70%, respectively, p < 0.001). Patients with HPV-negative OPC had significantly worse LRC compared to HPV-positive patients (67% and 90%, respectively, p < 0.001). The 3-year OS in HPV-positive group with leukocytosis compared to those without leukocytosis were 69% and 95%, respectively (p < 0.001). The figures for HPV-negative patients were 41% vs. 61%, respectively (p = 0.010). Conclusions: This is the first study to date reporting the independent impact of leukocytosis and HPV-status on outcome of patients with OPC. The poor outcome of patients with leukocytosis is mainly caused by the worse DC. The significant impact of leukocytosis on outcome was even more pronounced in HPV-positive patients. These biomarkers could help identifying patients with poor prognosis at baseline requiring intensification of local and/or systemic treatment while treatment de-intensification might be offered to the low-risk group.